KAJIAN PEMANFAATAN RUANG KEGIATAN KOMERSIAL KORIDOR JALAN TAMAN SISWA KOTA SEMARANG - Indra Wisnu Wardhana; Ragil Haryanto (Jurnal Pengembangan Kota, 2016)
One of the educational areas which have the function as the center of the new growth is the Campus of the State University of Semarang. The existence of Unnes trigger the development of the Sekaran sub-district. One area that has developed commercial activity quite rapidly in the Sekaran sub-district is the Taman Siswa Road Corridor. The purpose of this study was to assess the utilization of space commercial activity in the Taman Siswa road corridors and look for the cause of development of land in the region. The method used in this research is the method of quantitative analysis techniques using descriptive statistics. In the analysis that has been performed, on the factor analysis, the results are not as expected from researchers, or can be said output generated deviate from the input that has been inserted. This is because there are errors in data entry. To anticipate this is to use the results obtained from the descriptive statistical analysis.